Role of Mg ions in modulating the morphology and structure of CaCO3 crystals grown in aqueous foams - Rautaray, Debabrata; Kasture, Manasi; Sastry, M. (CrystEngComm, 2005)
We investigate the role of magnesium ions in modulating the morphology and crystallography of CaCO3 crystals grown in aqueous foam. This is accomplished by first making foams from an aqueous mixture of CaCl2+MgCl2 and the anionic surfactant aerosol-OT (AOT) followed by reaction of the foam with Na2CO3 solution. The Ca2+ and Mg2+ ions electrostatically complex with AOT and react with Na2CO3 within the foam to yield CaCO3 crystals of interesting morphology. These studies indicate that CaCO3 in a fractured, needle-like morphology was formed at high Mg2+ concentrations in the foam whereas porous, rhombic CaCO3 crystals were obtained at low Mg2+ concentrations. The effect of water drainage time and thereby, the structure of the foam on the morphology of the CaCO3 crystals grown was also studied.